Labial agglutination secondary to a herpes simplex II infection - DeMarco, B J; Crandall, R S; Hreshchyshyn, M M (American journal of obstetrics and gynecology, 1987)
A case is described of a young woman with labial agglutination secondary to a herpes simplex II infection that was successfully treated with laser vaporization.A case is described of a young woman with labial agglutination secondary to a herpes simplex II infection that was successfully treated with laser vaporization.